2008
DOI: 10.1007/s11373-008-9261-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: a biomarker of obesity-induced insulin resistance in adipose tissue and beyond

Abstract: Adiponectin is one of the most thoroughly studied adipocytokines. Low plasma levels of adiponectin are found to associate with obesity, metabolic syndrome, diabetes and many other human diseases. From animal experiments and human studies, adiponectin has been shown to be a key regulator of insulin sensitivity. In this article, we review the evidence and propose that hypo-adiponectinemia is not a major cause of obesity. Instead, it is the result of obesity-induced insulin resistance in the adipose tissue. Hypo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 165 publications
1
74
1
3
Order By: Relevance
“…ADPN may prevent the development of metabolic and atherosclerotic disorders and hypoadiponectinemia is currently considered a predictor of future cardiovascular events [9,10,28]. ADPN also plays an important role in myocardial remodeling [14][15][16]29].…”
Section: Discussionmentioning
confidence: 99%
“…ADPN may prevent the development of metabolic and atherosclerotic disorders and hypoadiponectinemia is currently considered a predictor of future cardiovascular events [9,10,28]. ADPN also plays an important role in myocardial remodeling [14][15][16]29].…”
Section: Discussionmentioning
confidence: 99%
“…38 Adiponectin is an adipokine that is produced by fat cells, which stimulates insulin sensitivity in muscle and fat cells. 39 On the other hand, alcohol may stimulate insulin sensitivity by increasing the secretion of insulin. In an acute model of alcohol treatment, Huang and Sjöholm 40 showed that alcohol promoted secretion of insulin by the pancreas, and that the increase in insulin secretion was linked to increased insulin sensitivity in alcohol-consuming animals.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss through energy restriction has a significant impact on improving cardiovascular disease (CVD) risk profile including favourable changes in adipokines (adiponectin and leptin), hyperlipidaemia, hypertension and insulin sensitivity (1,2). Weight loss also affects the insulin-like growth factor (IGF) system which can modulate carcinogenesis, CVD progression and longevity (3,4).…”
Section: Introductionmentioning
confidence: 99%